EVALUATING TOEFL PREDICTION TEST PROFICIENCY AMONG LECTURERS AND STUDENTS AT THE UNIVERSITY OF SAMUDRA - Bania, Allif Syahputra (University of Kuningan, 2024)
The TOEFL test to measure English language skills is an important determinant of educational success and admission to the university. The aim of study is to measure Toefl ability by lecturers and students at University of Samudra. This study used a test method with a quantitative-descriptive approach. With regard to the analysis of data from lecturers' TOEFL test results in various study programs, this study compared the scores for listening comprehension, reading comprehension and finally structure and written expression as well as showed the highest score, lowest scores and average scores obtained by the lecturers and students across disciplines. Meanwhile, analyzing data from the TOEFL test for students, this study demonstrated the highest, lowest and average scores of each study program in 5 faculties such as faculty of teacher training and education, faculty of engineering, faculty of law, faculty of agriculture, and faculty of economics. There were 16 lecturers who participated and 1.792 students. Finding found that the highest score of the lecturer's TPT test was 497 by P-15 from Accountancy. However, this highest score is not enough to pass doctoral studies with a minimum score of 500. So all lecturers must repeat the TPT test. Meanwhile, only Chemical and Technical Information managed to get an average score above 450 in order to meet the requirements of the thesis trial. Therefore, many lecturers and students did not pass the TPT test, so they repeated the TPT test.